Pengaruh Kualitas Layanan Terhadap Loyalitas Anggota Pinjaman Murabahah Pada Kopermas Borneo Sejahtera Di Kota Pontianak - Ni Gusti Ayu Made Frisca Deva Erica; Samsuddin Samsuddin; Sumiyati Sumiyati (Jurnal Produktivitas: Jurnal Fakultas Ekonomi Universitas Muhammadiyah Pontianak, 2019)
The purpose of this study was to determine the effect of service quality on the loyalty of Murabahah loan members at the Borneo Sejahtera Kopermas in Pontianak City. This research uses a descriptive method. The population in this study were members of the Kopermas Borneo Sejahtera who used Murabahah loans with a sample of 100 people. Data analysis performed is simple linear regression analysis, correlation coefficient, determination coefficient and model feasibility test.The results showed a simple linear regression equation, namely Ŷ = 2.545 + 0.364X. The results of the correlation coefficient show an R value of 0.606, which indicates that the relationship between service quality variables and the loyalty variable of members of the Borneo Prosperous Kopermas is strong. The results of the coefficient of determination show R2 value of 0.367 means that 36.7% loyalty of members of the Borneo Sejahtera Kopermas can be explained by the quality of service, while the remaining 63.3% loyalty of members of the Borneo Prosperous Kopermas is influenced by other variables not examined in this study. The results of the model feasibility test show the value of F count 19.382> F table 3.94, it can be concluded that a simple linear regression model can be used to predict member loyalty that is influenced by service quality.